Evaluation of biosolid fed by municipal waste-water sludge as a fertilizer in kale - Rocha, Ricardo Eiras Moreira da; Pimentel, Márcio Sampaio; Zago, Valéria Cristina Palmeira; Rumjanek, Norma Gouvêa; Polli, Helvécio De (Pesquisa Agropecuaria Brasileira, 2003)
This work aimed to evaluate the biosolid from the municipal waste-water treatment, as fetilizer in kale (Brassica oleraceae var. acephala, group Georgia). The experiment was in a randomized complete block design with three fertilization treatments, cattle manure, biosolid and urea, and four replications. Soil samples from each treatment were chemically, microbiologically and parasitologically analyzed. The heavy metal levels were below those recommended by the international legislation. After 45 days of incorporation of the biosolid into the soil, the fecal coliforms were almost undetectable. After 60 days, none of the samples showed the presence of eggs of parasitic worms, despite the high initial number. The plants fertilized with biosolid, at the higher level, showed greater productivity and lower N content in leaf tissue than those fertilized with cattle manure. The biosolid was classified as Class B, according to concentration of fecal coliforms, and is not appropriate for cultures with primary contact, as vegetables. The results show the importance to select indicators of sanity which provide biosolid safety use.